Diagnóstico e proposta de diretrizes para o gerenciamento de resíduos sólidos no município de Rio Claro (SP) - Mendes, Leonardo Mateus [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Over the last few years, Brazil has some problems related to the management of solid waste, mainly related to the final disposal of materials, resulting in serious environmental risks to the municipalities that suffer from this type of situation. Poorly designed landfills and weak management systems after the termination of their employment, for example, is currently showing as a major problem for urban expansion and the subsoil of these sites, endangering all the environmental quality of the areas where they are located . Because of this scenario, this work produced a diagnosis of the current situation of the management of solid waste in the city of Rio Claro (SP) from its generation, through selective collection and sorting, as well as its final destination, in order to propose a reflection on current form management, in order to present some guidelines based on Federal Law 12.305 / 2010 - National Solid Waste Policy for improvement of this issue in the city. Although the situation found in the city can be considered reasonable for good, there is a need to improve and how to manage, especially in the operational issue of selective collection and also the participation of society in the category Environmental Education, converging in the search for improvements to the common good

Ao longo dos últimos anos, o Brasil apresentou alguns problemas relacionados ao gerenciamento dos resíduos sólidos, principalmente relacionados à disposição final dos materiais, acarretando em graves riscos ambientais para os municípios que sofrem com este tipo de situação. Aterros mal planejados e com frágeis sistemas de gerenciamento após o encerramento de suas atividades, por exemplo, se mostram atualmente como um grande problema para a expansão urbana e para o subsolo destes locais, colocando em risco toda a qualidade ambiental das áreas em que se localizam. Devido a este cenário, este trabalho elaborou um diagnóstico da situação atual do gerenciamento dos resíduos sólidos no município de Rio Claro (SP) desde sua geração, passando pela coleta seletiva e triagem, e também sua destinação final, visando propor uma reflexão sobre atual forma de gerenciamento, a fim de apresentar algumas diretrizes com base na Lei Federal 12.305/2010 - Política Nacional de Resíduos Sólidos para melhoria desta questão no município. Embora a situação encontrada no município possa ser considerada de razoável para boa, há uma necessidade de melhora e na forma de gerenciar, principalmente na questão operacional da Coleta Seletiva e também na participação da sociedade no quesito Educação Ambiental, convergindo na busca de melhorias para o bem comum
Keywords: Política Nacional de Resíduos Sólidos (Brasil); Resíduos; Educação ambieental; Coleta seletiva de lixo; Gerenciamento de resíduos; Resíduos sólidos; Qualidade ambiental; Rio Claro (SP)